Dental management in palliative care of a patient with advanced oral cancer: A case report - Floriano, Tamires Feliciano; Heguedusch, Daniele; Pareja, Giovanna Nogueira; Oliveira, Samanta Vicente; Domaneschi, Carina; Gallo, Camila de Barros (Journal of Oral Diagnosis, 2021)
Tongue squamous cell carcinoma is one of the most prevalent and aggressive head and neck carcinomas. When diagnosed in an advanced stage is associated with a reduced overall survival rate due to the increased risk of locoregional recurrence and distant metastases. This article discusses the dental care strategies that were adopted regarding the progression to an incurable state of a 52-year-old man diagnosed with advanced tongue squamous cell carcinoma, which was initially treated with exclusive radiotherapy. In a 5-year-period, this patient developed severe lesions of osteoradionecrosis and also local tumor recurrence without the possibility of curative treatment. Palliative care in the dental context must be adopted in order to provide physical and emotional health still at the final moments in the patient’s life.